2022
DOI: 10.1007/s00477-022-02290-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term forecast improvement of maximum temperature by state-space model approach: the study case of the TO CHAIR project

Abstract: In the context of ''TO CHAIR'' project, this work aims to improve the accuracy of short-term forecasts of maximum air temperature obtained from the https://weatherstack.com/ website. The proposed methodology is based on a state-space representation that incorporates the latent process, the state, which is estimated recursively using the Kalman filter. The proposed model linearly and stochastically relates the forecasts from the website (as a covariate) to the observations of the maximum temperature recorded at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In comparison with other studies, the outliers occurrence here is similar to that that has been reported in other studies, both in "smart-cities" contexts (Csaji et A notable point of our work is the identification of the need for data filtering on temperature and PM data before outlier detection to omit extreme data. On temperature data, the filter should be adapted to the city's climate conditions (see also Pereira et al, 2023;Ma et al, 2017). PM should be eliminated at a range of 0-1,000 μm/m 3 , so extreme values can be excluded (see also Aix et One notable example is the presence of environmental phenomena that can be overshadowed by outliers and the methods used for their estimation and management.…”
Section: C Spatial Interpolation Of Datamentioning
confidence: 99%
“…In comparison with other studies, the outliers occurrence here is similar to that that has been reported in other studies, both in "smart-cities" contexts (Csaji et A notable point of our work is the identification of the need for data filtering on temperature and PM data before outlier detection to omit extreme data. On temperature data, the filter should be adapted to the city's climate conditions (see also Pereira et al, 2023;Ma et al, 2017). PM should be eliminated at a range of 0-1,000 μm/m 3 , so extreme values can be excluded (see also Aix et One notable example is the presence of environmental phenomena that can be overshadowed by outliers and the methods used for their estimation and management.…”
Section: C Spatial Interpolation Of Datamentioning
confidence: 99%
“…State-space models were originally developed in aerospace engineering in the early 1960s for the purpose of monitoring and correcting the trajectory of a spacecraft headed to the moon. Today, these models have wide applicability in many areas, such as finances [1], ecology [2], machine learning [3], and time series analysis and forecasting [4][5][6][7]. These models, associated with the Kalman filter algorithm [8], are a very powerful tool given their ability to update predictions both in real time and in a recursive procedure as new observations of the time series become available, thus improving the accuracy of predictions.…”
Section: Introductionmentioning
confidence: 99%